2015
DOI: 10.1007/s11356-015-5564-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the use of nanoimmobilized laccases to remove micropollutants from wastewater

Abstract: Enzymes immobilization is a useful way to allow enzyme reuse and increase their stability. A high redox potential laccase from Trametes versicolor (TvL) and a low redox potential, but commercially available low-cost laccase from Myceliophthora thermophila (MtL), were successfully immobilized and co-immobilized onto fumed silica nanoparticles (fsNP). Enzyme loads of 1.78 ± 0.07, 0.69 ± 0.03, and 1.10 ± 0.01 U/mg fsNP were attained for the optimal doses of TvL, MtL, and co-immobilized laccases, respectively. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…Batch degradation experiments were performed in order to assess the removal of micropollutants by Phoma sp., thereby verifying the activity of the fungus toward target pollutants at their environmentally relevant trace concentrations, and previously reported removal mechanisms involved [15]. Time courses of relative concentrations (initial = 100%; please refer to Supporting Information Table S1 for the corresponding absolute value) of DF, which is known to be directly oxidized by laccase [15,23,24], in batch tests employing active Phoma sp. with stimulated laccase production and in experiments containing the active fungus without stimulated laccase production are depicted in Fig.…”
Section: Micropollutant Removal By Phoma Sp In Municipal Wastewater supporting
confidence: 74%
“…Batch degradation experiments were performed in order to assess the removal of micropollutants by Phoma sp., thereby verifying the activity of the fungus toward target pollutants at their environmentally relevant trace concentrations, and previously reported removal mechanisms involved [15]. Time courses of relative concentrations (initial = 100%; please refer to Supporting Information Table S1 for the corresponding absolute value) of DF, which is known to be directly oxidized by laccase [15,23,24], in batch tests employing active Phoma sp. with stimulated laccase production and in experiments containing the active fungus without stimulated laccase production are depicted in Fig.…”
Section: Micropollutant Removal By Phoma Sp In Municipal Wastewater supporting
confidence: 74%
“…Laccases immobilized onto silica nanoparticles have been used to remove bisphenol from secondary effluent in a municipal wastewater treatment plant [96] as well as phenol from coking wastewater [97]. There are many studies on the synthesis and comparison of SENs with free enzymes; however, SEN applications for wastewater treatment are still in the rational design phase [98,99].…”
Section: Biocatalysts In Effluent Treatmentmentioning
confidence: 99%
“…The rationale behind the high activity yields is attributed to the fact that immobilized laccases on this type of support would have high affinity for standard substrates such as ABTS. For instance, Arca-Ramos et al [42] reported the hyperactivation of laccase from T. versicolor after the formation of covalent bonds with silica nanoparticles; whereas Matijosyte et al [11] described a similar behavior for laccase from T. villosa (activity recovery up to 148%) after the formation of cross-linking aggregates (CLEAS ® , CLEATechnologies, Delft, The Netherlands).…”
Section: Immobilization Of Laccase Onto Different Types Of Nanoparticlesmentioning
confidence: 99%
“…Lower activity of immobilized laccase towards phenolic substrates has also been previously reported. For instance, Arca-Ramos et al [42] found that bisphenol A degradation rate was much slower for immobilized laccases (from 6-to 26-fold lower than that of the free enzyme). This lower reaction rate was related to the potential aggregation of the nanoparticles which could reduce substrate accessibility.…”
Section: Biotransformation Of Phenol By Laccase Immobilized Onto Fsnpmentioning
confidence: 99%